2023
DOI: 10.2147/prbm.s394693
|View full text |Cite
|
Sign up to set email alerts
|

Visual Analysis of Psychological Resilience Research Based on Web of Science Database

Abstract: Background The importance of psychological resilience that people show in coping with stress and adversity is prominent, but few studies have used rigorous bibliometric tools to analyze the knowledge structure and distribution of psychological resilience research. Objective The purpose of this study was to sort out and summarize the previous studies on psychological resilience by using bibliometrics. Specifically, the time distribution of psychological resilience resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 79 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…Psychological resilience acts as an internal resource [48]. It mobilizes positive emotions to deal with stressful events and counteract the negative effects of stressors [49,50]. Bakker [51] suggested that the higher an employee's personal resources are, the more they are able to protect themselves from the demands of the job.…”
Section: The Mediating Role Of Psychological Resiliencementioning
confidence: 99%
“…Psychological resilience acts as an internal resource [48]. It mobilizes positive emotions to deal with stressful events and counteract the negative effects of stressors [49,50]. Bakker [51] suggested that the higher an employee's personal resources are, the more they are able to protect themselves from the demands of the job.…”
Section: The Mediating Role Of Psychological Resiliencementioning
confidence: 99%
“…As can be seen, the conceptualization and measurement of resilience can differ in significant ways with regards to e.g., adversity severity, focus on long-term development or in-the-moment reactivity, seeing resilience more as a personality trait or a dynamic reactivity at a certain point in time, and relying on retrospective cognitively reflected self-image or empirical data in the moment. Given that research on psychological resilience has proliferated during the last two decades (see Figure 1) (Su et al, 2023), it is imperative for the field to compare and contrast different operationalizations of the concept of resilience. For the current study, the main research question is as follows: how well are individual differences in reactivity to daily stressors captured by cross-sectional measures of resilience?…”
Section: Introductionmentioning
confidence: 99%